Characteristics of tobacco use among secondary school students: a cross-sectional study in a school in Valencia, Spain - Ribera-Osca, Joan Antoni; Carrion-Valero, Francisco; Martin-Gorgojo, Victor; Rando-Matos, Yolanda; Martin-Cantera, Carlos; Martin-Moreno, Jose M. (Frontiers in Public Health, 2023)
This epidemiologic, cross-sectional study aimed to identify characteristics associated with tobacco use in adolescents. The study sample included secondary school students aged 12-17 years in the 1st, 2nd, and 3rd grades of “Joan Fuster High School” in the city of Sueca, Valencia (Spain). An anonymous, self-administered questionnaire was used to collect data on demographics, smoking history, alcohol consumption, nicotine dependence, and exposure to parental smoking. The final sample of individuals surveyed included 306 students (50.6% females) with a median age of 13 years. The prevalence of smoking was 11.8% (13.5% in females and 9.9% in males). The mean age of smoking onset was 12.7 ± 1.6 years. Ninety-three students (30.4%) were repeaters, and 114 (37.3%) reported alcohol consumption. Significant factors associated with tobacco use were being a repeater (odds ratio [OR] 4.19, 95% confidence interval [CI] 1.75-10.55, p = 0.002), alcohol consumption (OR 4.06, 95% CI 1.75-10.15, p = 0.002) and parental smoking (OR 3.76, 95% CI 1.52-10.74, p = 0.007). An operational profile of features associated with tobacco consumption was identified in the presence of parental smoking, alcohol consumption, and poor academic performance. Consideration of these factors could be useful in the operational design of smoking cessation interventions for young people in a context where there is a great need for better prevention and control of smoking.